Legal Protection of Child Adoption without Trial by Human Rights Perspective - Djaini, Alan; Wantu, Fence M.; Tijow, Lusiana Margareth (Universitas Negeri Gorontalo, 2021)
This research aims to describe and analyze legal protection issues as regards child adoption without trial from a human rights perspective. It is descriptive-qualitative empirical research. It applies a socio-legal approach and case approach. Results demonstrate that child adoption without trial may breed the following legal consequences: misunderstanding what is permissible and what is not from an Islamic point of view, interfering with family relationships and their rights, and fueling disputes between family members. These legal consequences happen as adoptive parent candidates are not well educated attributed to procedures for child adoption. Child adoption is also mentioned in the Law of the Republic of Indonesia Number 39 of 1999. The government, state, parents, and society shall not neglect and are obliged to concern about children’s rights by endeavoring to make the legality of the child’s identity status in the form of a birth certificate citation document.